Pengaruh penggantian Bovine Serum Albumin (BSA) dengan putih telur pada pengencer CEP-2 terhadap kualitas semen sapi Peranakan Ongole pada suhu penyimpanan 3-5oC - Nisa’us Sholikah; Nurul Isnaini; Aulia Puspita Anugra Yekti; Trinil Susilawati (Faculty of Animal Science, Universitas Brawijaya, 2016)
Purpose of this research was to investigate the effect of Bovine Serum Albumin substitution by albumen on CEP-2 to semen quality Ongole CrossBred bull stored at 3-5oC. Research was conducted at Research Centre Beef Cattle Laboratory, Grati, Pasuruan on February 2016. Semen diluent was divided into two groups, there were P0 (90% CEP-2 + 10% Egg Yolk (EY)); and P1 (90% CEP + 0.4% albumen + 10% EY). Data of the research were analyzed using paired design t test. The result showed that after eight days chilled preservation, percentage of motility P1 (47.4±10.9%) was higher than P0 (47±9.2%). Percentage of viability P0 (83.1±1.9%) was higher than P1 (81.3±1.5%). Percentage of abnormality P1 (3.6±0.4%) was lower than P0 (3.8±0.3%). Total motile sperm count after six days chilled preservation was significantly higher in all treatments compared to the standard criteria of SNI 40% motile sperm/ml. The conclusion of this research was 0,4% albumen could replace the BSA capability on CEP-2. Keywords: CEP-2, Bovine Serum Albumin, chilled preservation, semen quality